The Mediating Role of Customer Satisfaction in The Relationship Between Service Quality and Complaint Handling Toward Customer Loyalty at Bank After Digital Disruption - Mansur Chadi Mursid; Elysia Anindya Indriani; Pratomo Cahyo Kurniawan; Catherine Conales Salvo; Aenurofik Aenurofik; Abdul Hamid (Business and Applied Management Journal, 2026)
The development of digital transformation in the banking industry has encouraged Bank Syariah Indonesia (BSI) to digitally transform its mobile banking services by releasing the BYOND by BSI SuperApp as the latest version of BSI Mobile. However, in early 2025, a digital service disruption occurred, leading to an increase in customer complaints, including at Bank BSI. This disruption caused inconvenience in transactions and potentially affected customer satisfaction and loyalty. The purpose of this study was to evaluate the extent to which service quality and complaint handling influenced customer loyalty through customer satisfaction. This study used a quantitative approach with a survey method. Data were collected by distributing questionnaires to BSI KCP Pemalang customers using a purposive sampling technique. The sample of this study were BYOND users who were affected by the disruption, had previously reported problems related to BYOND, were at least 18 years old, and lived in the Pemalang area. The measurement scale used a five-point Likert scale. Data analysis was performed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the SmartPLS 4 application. The results showed that service quality and complaint handling influenced customer satisfaction. However, service quality and complaint handling did not influence customer loyalty. Customer satisfaction was shown to influence loyalty and mediate the relationship between service quality and complaint handling on customer loyalty with p values 0,001 and 0,003. The practical implication of this research is the importance of prioritizing consumer satisfaction in handling their complaints.